2022
DOI: 10.1002/app.53034
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity and insulation properties of mica tape with BN coating via electrostatic spraying technology

Abstract: The bottleneck problem of the development of high‐voltage motors to a larger capacity can be solved if the thermal conductivity is improved without sacrificing the insulation characteristics of the main insulation material. In this paper, a spraying technology based on electrospinning is proposed that can evenly spray boron nitride (BN) with high thermal conductivity onto the surface of mica tape. With the increase in BN content, the insulation and thermal conductivity of mica tape are optimized to varying deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…We found that the temperature variation at the left and right edges of the rectangular LSMO is higher, which might be due to the difference in thermal conductivity. According to previous reports [62][63][64], the thermal conductivity of LSMO (1-3 W/m⋅K) and Mica (~ 0.5 W/m⋅K) is substantially higher than that of air (~ 0.026 W/m⋅K), resulting in difficulty for heat dissipation at the edges of LSMO than its middle.…”
Section: Resultsmentioning
confidence: 92%
“…We found that the temperature variation at the left and right edges of the rectangular LSMO is higher, which might be due to the difference in thermal conductivity. According to previous reports [62][63][64], the thermal conductivity of LSMO (1-3 W/m⋅K) and Mica (~ 0.5 W/m⋅K) is substantially higher than that of air (~ 0.026 W/m⋅K), resulting in difficulty for heat dissipation at the edges of LSMO than its middle.…”
Section: Resultsmentioning
confidence: 92%
“…Electronic packaging materials, as an important part of chip protection, play a major role in protecting core components 1 . However, with the dramatically demand for mobile and portable devices as well as electronic device power consumption, thermal conductivity and insulation performance have become another major attribute of electronic packaging materials 2 . This has also become the focus of addressing such thermal interface materials (TIMs) at present.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, BN has a high thermal conductivity, which makes it an excellent candidate for use in heat dissipation applications, such as thermal management of electronic devices, and for use as a substrate for high-power electronic devices [ 9 , 10 ]. Secondly, BN is an excellent insulator, which makes it ideal for use in high-voltage applications, such as power distribution systems [ 11 ]. Thirdly, BN has a high strength-to-weight ratio and excellent mechanical stability [ 12 ], which makes it a suitable material for use in lightweight structures for aerospace and drone applications.…”
Section: Introductionmentioning
confidence: 99%